From Marshall Plan to “Hilton in the wild”: The Transnational History of a Cooperative Housing Block in Esat, Ankara - Sıla Karataş (ABE Journal)
This paper concerns the planning, design, and construction history of a postwar multifamily housing block in Ankara, Turkey, viewed from the perspective of the transnational and local networks behind its realization. Built by the Mintrak Building Cooperative (1957-1962) founded by executive engineers and managers of TürkTraktör, Turkey’s first tractor manufacturing company established as part of the Marshall Plan (1948-1952), the block is one of the local examples of the International Style built throughout the country. It was the tallest housing block in the Esat neighborhood, with a reinforced concrete structural framework, pilotis, and a terraced roof with communal spaces. Besides adopting the formal characteristics and common construction materials of its time, as this paper suggests, the building is emblematic of the postwar housing production from policy and development to design, construction, and domestic culture. Built as part of a workers’ housing cooperative advocated by postwar housing policy yet founded by the executives and US-educated employees of a transnational company, the block exemplifies postwar Americanization in Turkey in terms of transnational and local exchanges and their urban, architectural, and social imprints. Through content analysis based on archival sources, official reports and architectural drawings as well as oral testimonies collected from cooperative members and residents of the building, this paper questions the transnational extent of the Marshall Plan, to which a local housing cooperative could represent. It provides an in-depth analysis of the technocratic making of the housing block, through all different stages of its development, from founding “the cooperative in the wild” to building “Esat’s Hilton,” as its initiators and residents called it. In this respect, the paper argues that the block is a transnational prototype of US-guided local modernization, based on the US-promoted self-help model that introduced an autonomous organization to housing production in Turkey.